2000
DOI: 10.1006/obhd.2000.2896
|View full text |Cite
|
Sign up to set email alerts
|

A Longitudinal Field Investigation of Gender Differences in Individual Technology Adoption Decision-Making Processes

Abstract: This research investigated gender differences in the overlooked context of individual adoption and sustained usage of technology in the workplace using the theory of planned behavior (TPB). User reactions and technology usage behavior were studied over a 5-month period among 355 workers being introduced to a new software technology application. When compared to women's decisions, the decisions of men were more strongly influenced by their attitude toward using the new technology. In contrast, women were more s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

26
469
11
8

Year Published

2006
2006
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 933 publications
(514 citation statements)
references
References 87 publications
(124 reference statements)
26
469
11
8
Order By: Relevance
“…Their primary conclusions are that perceived behavioural control makes a significant positive contribution to predicting the behavioural intention of the violations studied, and social norms have only a small influence on intentions. Venkatesh, Morris and Ackerman (2000) show that in technology adoption decisions, men are more strongly influenced by their attitude toward using new technology, whereas women are more strongly influenced by the social norms and perceived behavioural control. This finding suggests that other factors can influence the relationship between attitudes, social norms, perceived behavioural control and intention.…”
Section: The Theory Of Planned Behaviourmentioning
confidence: 93%
“…Their primary conclusions are that perceived behavioural control makes a significant positive contribution to predicting the behavioural intention of the violations studied, and social norms have only a small influence on intentions. Venkatesh, Morris and Ackerman (2000) show that in technology adoption decisions, men are more strongly influenced by their attitude toward using new technology, whereas women are more strongly influenced by the social norms and perceived behavioural control. This finding suggests that other factors can influence the relationship between attitudes, social norms, perceived behavioural control and intention.…”
Section: The Theory Of Planned Behaviourmentioning
confidence: 93%
“…We found that the structures of legitimation were significant in explaining loyal use for novices and those with less than five years of experience. Prior research with cognitive models of use have observed that social norms are important in the initial adoption decision but that their impact fades away (usually to insignificance) the longer one uses an information system (Venkatesh et al, 2000b). The initial test of UTAUT, for example, found no significant effects of norms three months after system implementation except for four-way interactions with gender, age, and voluntariness (see time period T3 in Venkatesh et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…Second, most technology use theories focus on initial adoption (Venkatesh et al, 2003). However, research shows that users' beliefs change over time, so models designed for initial adoption may not fit ongoing use (Bhattacherjee & Premkumar, 2004;Venkatesh, Davis, & Morris, 2000a;Venkatesh, Morris, & Ackerman, 2000b).…”
Section: Prior Research On Technology Usementioning
confidence: 99%
“…Building on previous work Venkatesh, Morris, & Ackerman, 2000), UTAUT presents a moderating effect of gender in the relationships between performance expectancy and behavioral intention, such that it becomes stronger for men; and effort expectancy and behavioral intention, such that it is more significant for women (Venkatesh et al, 2003). Gender differences are useful in that they can propel research into an area by putting in evidence the existence of an underlying dynamic (Halpern, 1992).…”
Section: Introductionmentioning
confidence: 94%